The Agency of Place: Toward a More-Than-Human Geographical Self. Issue 1 (2nd January 2016) - Larsen, Soren C.; Johnson, Jay T.
Abstract : Contemporary Indigenous activism asserts an agency for place not normally found in geographical scholarship. Through place-based protest, organizing, and direct action, Native and non-Native people are interacting with place as a conscious being with the capacity to speak, create, and teach the responsibilities required for more inclusive forms of coexistence in today's settler states. This "placework" articulates a more-than-human geographical self whose subjectivities are grounded in, and accountable to, land-based relationships and knowledges. Placework contributes to a geographical posthumanism that offers a distinctively Indigenous approach to the predicaments of the Anthropocene.